Age and clinical signs as predictors of COVID-19 symptoms and cycle threshold value. Issue 1 (1st January 2022) - Dergaa, Ismail; Abubaker, Muneer; Souissi, Amine; Mohammed, Abdul Rafi; Varma, Amit; Musa, Sarah; Al Naama, Abdullah; Mkaouer, Bessem; Ben Saad, Helmi
ABSTRACT: Many COVID-19 infected people remain asymptomatic, and hence the diagnosis at first presentation remains a challenge. Assessment at a presentation in primary care settings is usually done by visual triaging and basic clinical examination. This retrospective study involved investigating the medical e-records of COVID-19 positive patients who presented to a COVID-19 centre in Qatar for July 2020. The presence (symptomatic group) or the absence (asymptomatic group) of symptoms along with objective vital examination ( ie ; heart-rate (HR), temperature, haemoglobin saturation (SpO2 )) were analysed and linked to the viral load ( ie ; cycle threshold (Ct)) of COVID-19 positive patients. Four hundred eighty-one symptomatic (230 males) and 216 asymptomatic (101 males) patients were included. Compared to the asymptomatic male group, the symptomatic male group was older, had lower Ct value and SpO2, and higher temperature and HR. Compared to the females asymptomatic group, the symptomatic females group had lower Ct value, and higher temperature. Compared to the asymptomatic group, the symptomatic group had lower Ct value and SpO2, and higher temperature and HR. Compared to the asymptomatic group, the symptomatic group had lower Ct values (age groups [21–30], [31–40], [41–50] and [51–60]), higher temperature (age groups [21–30] and [31–40], Ct ranges [20.01–25.00] and [25.01–30.00]), higher HR (age groups [21–30] and [31–40], Ct range [15.01–20.00]); and lower SpO2 (age groups [41–50] and [51–60], Ct ranges [15.01–20.00] and [35.01–40.00]). Compared with asymptomatic patients, symptomatic patients with COVID-19 are most likely to be febrile, tachycardic, hypoxic and having higher viral load. Higher viral load was associated with higher HR, higher temperature, lower SpO2, but there was no relation between viral load and age.